ANALISIS PENGARUH VARIABEL-VARIABEL FUNDAMENTAL DAN TEKNIKAL TERHADAP HARGA SAHAM - Dwi - Wulandari; Sumiaty - -; Hary - Susanto (Sekolah Pascasarjana Universitas Brawijaya, 2009)
ABSTRACT Research objective is to analyze effects of fundamental variables on the share-price of the go public textile companies at the BEJ. Survey was conducted in the 25 unit of textile companies at the BEJ. Research results show that share-price of the textile companies significantly was influenced by the all independent variables simultaneously. The two dominan variables are circulated money (X6) and the last share-price (X9). Effects of the circulated money suggest the negative direction, and effect of the last share-price suggest a dominan positive direction. A determination coefficient about 0.917 suggest a good contribution of the last share-price. A linear regression model can be used in estimating fluctuation pattern of the share price. Keywords: share-price, textile company